Aspects Concerning "Play" for the Promotion of Preschool Children with Severe Speech- and Language Impairment - Dieter Ullrich; Magret Marten (MDPI AG, 2016)
Speech and language abilities are of great importance for later participation in economical and social life. In Lower Saxony/Germany, severely speech-/language (SL) impaired children may obtain special treatment during preschool in a so-called "Sprachheilkindergarten" (STK), a kindergarten focusing on early SL therapy. Purpose: This work analyzes the role of play during SL-therapy at the STK and monitors the long-term development and success of SL-impaired children. Methods: Long-term development (up to 19 years) of 71 children, who were dismissed from a STK during 1993 and 2006, was investigated. Playing habits were observed in 21 children (male: n = 14, female: n = 7), who were treated at STK in the years 2011/2013. The study was designed as a register study. Results: Approximately 75% of the children attend a regular school or complete a standard professional training after being treated at the STK. Upon admittance, 100% of the children had severe SL impairment, in addition 75% of the children exhibit deranged, not age-appropriate playing behavior. Additionally, children often show indication of social-emotional problems. At dismissal from the STK, the children show measurable improvement of SL and playing abilities due to SL therapy and educational measures. But according to the present study there were no close statistical relations between play- and SL development. Conclusion: Due to active promotion and therapy, many children achieve to improve their SL and playing abilities. The apparent independent improvement of these skills allows them to catch up with other children in their age group. Potentially, this is the crucial aspect for a child's long-term development as it profits from its peer group.